Analysis of Odor Components in Salted Egg Yolk during Thermal Processing Using Gas Chromatography-Mass Spectrometry and Multivariate Statistical Analysis - LI Xiangyu, XIONG Yating, TENG Jianwen, WEI Baoyao, HUANG Li, XIA Ning (Shipin Kexue, 2023)
Odor compounds produced in salted egg yolk during thermal processing were identify by sensory evaluation and gas chromatography-mass spectrometry (GC-MS) combined with multivariate statistical analysis such as hierarchical cluster analysis (HCA), orthogonal partial least squares-discriminant analysis (OPLS-DA) and principal component analysis (PCA). By using quantitative descriptive sensory analysis, it was found that there was a significant difference in the flavor profile between egg yolk samples with and without unpleasant odor, and it was determined that some egg yolks had obvious off-flavor during hot processing. Cluster analysis showed that the six groups of salted egg yolk samples were clearly divided into two categories, which was consistent with the sensory evaluation results. Furthermore, OPLS-DA identified 33 major differential components with variable importance in the projection (VIP) scores greater than one between samples with and without unpleasant odor, and aldehydes and alcohols were the most significant differential components. Finally, the volatile compounds showing a positive correlation with sour odor were screened by PCA, and n-hexanal, n-valeraldehyde, 1-octen-3-ol, trans,trans-2,4-decadienal, styrene, dimethyl disulfide and 2-nonone were identified due to their odor activity values (OAV) greater than one as the major odor compounds of salted egg yolk during thermal processing. The results provide a reference for analysis of the flavor characteristics and possible off-flavor components of salted egg yolk after thermal processing and provide a scientific basis for accessing the quality of salted egg yolk.